A surface proton antenna in carbonic anhydrase II supports lactate transport in cancer cells - Noor, Sina Ibne (eLife, 2018)
Many tumor cells produce vast amounts of lactate and acid, which have to be removed from the cell to prevent intracellular lactacidosis and suffocation of metabolism. In the present study, we show that proton-driven lactate flux is enhanced by the intracellular carbonic anhydrase CAII, which is colocalized with the monocarboxylate transporter MCT1 in MCF-7 breast cancer cells. Co-expression of MCTs with various CAII mutants in Xenopus oocytes demonstrated that CAII facilitates MCT transport activity in a process involving CAII-Glu69 and CAII-Asp72, which could function as surface proton antennae for the enzyme. CAII-Glu69 and CAII-Asp72 seem to mediate proton transfer between enzyme and transporter, but CAII-His64, the central residue of the enzyme’s intramolecular proton shuttle, is not involved in proton shuttling between the two proteins. Instead, this residue mediates binding between MCT and CAII. Taken together, the results suggest that CAII features a moiety that exclusively mediates proton exchange with the MCT to facilitate transport activity.